2017
DOI: 10.1016/j.atmosenv.2017.06.047
|View full text |Cite
|
Sign up to set email alerts
|

An example of aerosol pattern variability over bright surface using high resolution MODIS MAIAC: The eastern and western areas of the Dead Sea and environs

Abstract: The extreme rate of evaporation of the Dead Sea (DS) has serious implicatios for the surrounding area, including atmospheric conditions. This study analyzes the aerosol properties over the western and eastern parts of the DS during the year 2013, using MAIAC (Multi-Angle Implementation of Atmospheric Correction) for MODIS, which retrieves aerosol optical depth (AOD) data at a resolution of 1km. The main goal of the study is to evaluate MAIAC over the study area and determine, for the first time, the prevailing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 58 publications
2
8
0
1
Order By: Relevance
“…For example, Kloog et al (2015) found r pearson = 0.85 between MAIAC/Aqua and AERONET data for Israel; Emili et al (2011) reported a similar adjusted linear model coefficient (R 2 adj = 0.67) in Ispra (Italy). Similar results were also found using AERONET sites in the East Coast of the United States (Lyapustin et al, 2011) and above arid (bright) areas surrounding the Dead Sea (Sever et al, 2017). Slightly higher correlations coefficients (up to r > 0.9) were found by Martins et al (2018) comparing MAIAC-Terra to two AERONET sites in the Amazon in the period 2011-2015.…”
Section: Assessment Of the Maiac Aod Accuracy In Córdobasupporting
confidence: 77%
See 1 more Smart Citation
“…For example, Kloog et al (2015) found r pearson = 0.85 between MAIAC/Aqua and AERONET data for Israel; Emili et al (2011) reported a similar adjusted linear model coefficient (R 2 adj = 0.67) in Ispra (Italy). Similar results were also found using AERONET sites in the East Coast of the United States (Lyapustin et al, 2011) and above arid (bright) areas surrounding the Dead Sea (Sever et al, 2017). Slightly higher correlations coefficients (up to r > 0.9) were found by Martins et al (2018) comparing MAIAC-Terra to two AERONET sites in the Amazon in the period 2011-2015.…”
Section: Assessment Of the Maiac Aod Accuracy In Córdobasupporting
confidence: 77%
“…Recently, a high-resolution algorithm (Multi-Angle Implementation of Atmospheric Correction, MAIAC) providing AOD at 1km-resolution was developed (Lyapustin et al, 2011 and, thus representing a promising tool to investigate atmospheric particles variability at the city scale (Chudnovsky et al 2013a). It has been already usefully employed investigating different areas of the world such as the United States (Chudnovsky et al, 2014;Lee H. et al, 2011;Lee M. et al, 2016), the Amazon region (Martins et al, 2018), Europe (Arvani et al, 2016;Emili et al, 2011;Stafoggia et al, 2017), the Middle East and Asia (Kloog et al, 2015;Sever et al, 2017;Xiao et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, many satellites provide reliable AOD (aerosol optical depth) products that can be used through various techniques for PM estimations from space, such as the Advanced Very High Resolution Radiometer (AVHRR) [20,21], Multiangle Imaging Spectroradiometer (MISR) [22], Medium Resolution Imaging Spectrometer (MERIS) [23], Spinning Enhanced Visible and Infrared Imager (SEVIRI) [24] and Moderate Resolution Imaging Spectroradiometer (MODIS) [25][26][27][28]. Among the satellite data products, AOD provided by MODIS sensor on board Terra and Aqua satellites has been widely used for many applications due to its high retrieval accuracy over land and near daily global coverage at 10 km and 3 km spatial resolution [26,27,29].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, remote sensing (RS) technology is an important means to detect and monitor aerosol based on the AOD ( Badarinath et al, 2011 ; Ge et al, 2011 ; Ginoux et al, 2001 ; Huang et al, 2007 , 2009 ; Masoumi et al, 2013 ; Perry, Cliff & Jimenez-Cruz, 2004 ; Sever et al, 2017 ; Tegen & Fung, 1994 ; Wang et al, 2010 ). As a column-integrated quantity, AOD reflects aerosol column loading and the impact of aerosols on Earth’s radiation budgets ( Park, Ahn & Chang, 2007 ).…”
Section: Introductionmentioning
confidence: 99%